Studies on Neotropical crickets: A new Perugryllae cricket (Orthoptera: Gryllidae: Gryllinae: Gryllini: Brachytrupina) from the foothills of the Colombian Andes - Cadena-Castañeda, Oscar J.; Quintana-Arias, Ronald Fernando; Tavares, Gustavo Costa (Zootaxa, 2023)
A new tiny field cricket species of the genus Laureopsis (Orthoptera: Gryllidae), from the foothills of the Colombian Andes is described. With the description of Laureopsis andinus n. sp., the distribution of the Perugryllae Group expands outside the Amazon rainforest of Colombia and Peru, and is recorded for the first time in areas of Andean influence. A distribution map and a key for the identification of the species of the group are also provided. Finally, the morphology and distribution of the species of the two genera known for the Perugryllae group are discussed.